PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP NILAI-NILAI PANCASILA SISWA DI KELAS II SDK DON BOSKO 4 KOTA KUPANG - Devita Memo, Maria; Ly, Petrus; K. Kota, Martha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research entitled “The Effect of the Role-Playing Learning Model on Improving Students’ Conceptual Understanding of Pancasila Values in Grade II at SDK Don Bosko 4” was motivated by the low ability of Grade II students at SDK Don Bosko 4 in understanding the concept of Pancasila values. This was based on the results of a preliminary observation, which found that only 40% of students achieved the Minimum Competency Criteria (KKTP), while the remaining 60% did not. This study employed a quantitative research approach that emphasizes the analysis of numerical data obtained through statistical techniques. The sample used in this study consisted of all 20 Grade II students. There were two variables in this study, namely the role-playing model as the independent variable and conceptual understanding as the dependent variable. The data collection techniques used were tests, observation, and documentation. The data analysis techniques included normality testing and hypothesis testing. The results of the normality test showed a significance value of 0.065 for the pretest data and 0.204 for the posttest data. Meanwhile, the hypothesis test showed that the mean score of the pretest was 46.50 and the mean score of the posttest was 77.50. The increase in the mean score from pretest to posttest was 66.67%. Based on these findings, it can be concluded that the role-playing learning model is effective in improving students’ conceptual understanding of Pancasila values.